Physicochemical properties, crystal structures, antibacterial properties and in silico characterization of cobalt and copper metal complexes and their acido complex crystals with 4-chloromethylpyridine. (1st November 2022) - Matshwele, James T.P.; Nareetsile, Florence; Tebogo, Masego; Mazimba, Ofentse; Masita, Fortunate P.; Julius, Lebogang; Jongman, Mosimanegape; Odisitse, Sebusi
Graphical abstract: The synthesis of datively bonded complexes to 4-picloyl chloride and their acido complex counterparts of the type [MCl4 ] 2− were synthesized, characterized using SC-XRD, UV/Vis, FTIR, Computational methods, Thermal techniques and elemental analysis. These techniques helped describe their physicochemical properties. Further, their antibacterial properties towards Gram-negative and positive drug resistant bacteria is discussed. Abstract: The physicochemical and antibacterial properties of compounds of copper and cobalt of the type (4PY-H)2 [MCl4 ] and [M(Cl)2 (4PY)2 ] were studied. The conventional coordination compounds and the acido complex crystals were prepared in a 1:2 mol ratio. The magnetic and electronic spectra data of the copper compounds showed that the two behave similarly to each other, even though, the copper acido complex had better absorptive properties. The copper acido complex crystalized in the monoclinic Ia space group, while the copper complex crystalized in the triclinic P 1 space group. The cobalt complex similarly crystalized in the triclinic P 1 space group while its acido complex crystalized also crystalized in a monoclinic crystal system, but contrary to the copper acido complex crystal, it was under P 21 / c space group. FTIR indicated that the compounds were structurally different where the acido complexes and the free ligand both displayed NH peak in their IR spectra. This proved the existence of a protonated pyridyl nitrogen. Additionally, In silico geometry and FTIR data of all the 4 compounds corroborated well with the experimental data. The two compounds had very different melting points where the complex melted at higher temperatures than the acido complex. The compounds were thermally stable with melting points above 100 °C with complexes having higher melting points than acido complex crystals for both copper and cobalt. Also, DSC profiles showed that with increase in heat the acido complex crystals transformed to their complex forms. The antibacterial activity studies showed that the cobalt compounds were more active against the Gram-negative bacteria with more activity towards K. pneumoniae while the copper compounds were more active against the Gram-positive especially towards S. aureus. The time kill kinetics showed all the copper compounds to be bactericidal while the cobalt compounds were bacteriostatic.